A review of technological capability in Malaysian manufacturing sector - Ahmad, Nurazwa; Othman, Siti Norezam; Mad Lazim, Halim (2012)
Today, manufacturing industry plays a crucial role of the economy in most countries. Due to the dynamic nature of manufacturing, its market and environmental situations, manufacturing firms are facing a serious and great importance challenges. Malaysia is striving to compete in the global market and therefore have to maintain and boost local industries for economic strengthen. The economic expert of the country had advised local companies to strengthen and upgrade their technological capabilities in order to achieve better economic performance. As the technological capability involved in the production and operation which are the cornerstones of every manufacturing company, therefore it should then be improved and monitored periodically. Substantial bodies of literatures on technological capability predominantly have investigated on various roles of the capability, to some point it shows the importance of technological capability acquisition for industrial development. However, the creation of technological capability is not a short term commitment. It takes effort on every aspect to realize its effects on the performance of organizations while gaining competitive advantages and sustaining commercial success in the local and global market along their operational period. Based from the resource-based view theory, the main idea of this paper is to review on how technological capability gives an impact towards manufacturing performance of Malaysian manufacturers. Finally, this paper will identify the measurements of manufacturing performance which are important to be scrutinized in manufacturing plants hence to improve their operational and production performance therefore achieved competitive advantages.